1998
DOI: 10.1046/j.1365-2249.1998.00586.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased eosinophil activity in acutePlasmodium falciparuminfection—association with cerebral malaria

Abstract: To assess the eosinophil response to Plasmodium falciparum infection a cohort of initially parasite-free Ghanaian children was followed for 3 months. Seven of nine children who acquired an asymptomatic P. falciparum infection showed increase in eosinophil counts, while a decrease was found in seven of nine children with symptomatic malaria, and no change was observed in 14 children who remained parasite-free. In a hospital-based study, paediatric patients with cerebral malaria (CM), severe anaemia (SA), or unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 23 publications
(25 reference statements)
4
36
0
6
Order By: Relevance
“…Eotaxin is well recognized as a potent chemoattractant for eosinophils (46,47). Although eosinophil accumulation was not compared in WT versus Tbx21 2/2 mice, it has previously been reported that Ghanian pediatric patients with CM had uniformly low eosinophil counts because of tissue sequestration and destruction rather than decreased production during acute illness followed by eosinophilia 30 d after cure (48). Importantly, the eotaxin receptor is expressed by Th2 CD4 + T cells, and eotaxin is critical for the generation and maintenance of Th2 cells at allergenic sites and promotes the production of IL-4 and IL-5 (49,50).…”
Section: Figurementioning
confidence: 99%
“…Eotaxin is well recognized as a potent chemoattractant for eosinophils (46,47). Although eosinophil accumulation was not compared in WT versus Tbx21 2/2 mice, it has previously been reported that Ghanian pediatric patients with CM had uniformly low eosinophil counts because of tissue sequestration and destruction rather than decreased production during acute illness followed by eosinophilia 30 d after cure (48). Importantly, the eotaxin receptor is expressed by Th2 CD4 + T cells, and eotaxin is critical for the generation and maintenance of Th2 cells at allergenic sites and promotes the production of IL-4 and IL-5 (49,50).…”
Section: Figurementioning
confidence: 99%
“…In addition, eotaxin is a strong chemoattractant for (42), which are also associated with allergic reactions (44). However, eosinophil responses have been reported during malaria infections (25) and are important for producing functional IL-13 (44). Since eosinophil responses are associated with hematological recovery following malarial treatment (8) and Hb levels typically decrease following successful parasite clearance with antimalarial drugs (7), it is tempting to postulate that the IL-13/eotaxin pathway may negatively regulate Hb levels during a malaria infection through eosinophilic responses.…”
Section: Vol 79 2011 Biomarkers For Malarial Anemia Severity 4677mentioning
confidence: 99%
“…Since eosinophil responses are associated with hematological recovery following malarial treatment (8) and Hb levels typically decrease following successful parasite clearance with antimalarial drugs (7), it is tempting to postulate that the IL-13/eotaxin pathway may negatively regulate Hb levels during a malaria infection through eosinophilic responses. Kurtzhals et al (25) observed that during acute infection, eosinophils were sequestered in deep tissues, while recent studies showed that the production of high levels of IL-13 in malaria-infected children was associated with hepatomegaly (52). Eosinophils are known to produce granule proteins (e.g., eosinophil cationic protein [ECP]) whose levels are correlated with TNF-␣ and IL-2R during malarial infections (25).…”
Section: Vol 79 2011 Biomarkers For Malarial Anemia Severity 4677mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there is suggestion that histamine might influence the polarization of T-helper cell development through inhibitory effects on dendritic cells (Idzko et al, 2002). Reports indicate that specific components of the innate immune system, including eosinophils (Kurtzhals et al, 1998), basophils (Nyakeriga et al, 2003), and Mast cells (MCs) (Furuta et al, 2006), could play important roles in the pathogenesis of malaria. Increased levels of histamine in plasma and tissue, derived from basophils and MCs, notably following stimulation by IgE through the high affinity receptor FcεR1, are associated with the severity of disease in humans infected with P. falciparum and in animal malaria models (Bhattacharya et al, 1988;Srichaikul et al, 1976).…”
Section: Role Of Allergy In Malariamentioning
confidence: 99%